Differential branching fraction and angular analysis of the decay B 0 → K * 0 μ + μ - - Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; Alkhazov, G; et al. (2013)
The angular distribution and differential branching fraction of the decay B 0→ K * 0 μ + μ - are studied using a data sample, collected by the LHCb experiment in pp collisions at S=7 TeV, corresponding to an integrated luminosity of 1.0 fb -1. Several angular observables are measured in bins of the dimuon invariant mass squared, q 2. A first measurement of the zero-crossing point of the forward-backward asymmetry of the dimuon system is also presented. The zero-crossing point is measured to be q02=4.9± 0.9 GeV2 c4, where the uncertainty is the sum of statistical and systematic uncertainties. The results are consistent with the Standard Model predictions. [Figure not available: see fulltext.] © 2013 Cern for the benefit of the LHCb collaboration.